PENGARUH SISTEM FULLDAY SCHOOLTERHADAP PRESTASI BELAJAR SISWA KELAS X PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMANEGERI 02 SINGINGI KABUPATEN KUANTAN SINGINGI - Siti Latifatun Munawaroh (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
The problem in this study is the failure to achieve the full day school system which is expected to increase student effectiveness, full learning hours, so that students cannot follow the logging process effectively, Lack of PAI learning media makes students not creative in the learning process. students become uncontrolled and measured in learning, and often do not make assignments at home .. In general, this study aims to determine the effect of the Fullday School System on Learning Achievement of Class X Students in the Subject of Islamic Religious Education at SMAN 02 Singingi, Kuantan Singingi Regency. The research method used is quantitative research, the population of this study was 133 students, while the sample the authors took as much as 50% of the total sample 68 students studied and 1 teacher PAI. Data collection techniques using, observation, interviews, documentation and questionnaires. The data analysis technique used is a simple linear regression technique. After calculating, the authors conclude that,